Behavioural perspective of individuals towards mutual fund investments – a critical analysis - MS. B. NEERAJA; MS. E. AYSHWARYA (The journal of contemporary issues in business and government, 2020)
In this research study we are getting to see about mutual funds in India. There are many investments in India like equity share, mutual fund, fixed deposit, public provident fund, land, gold, etc. open-end fund may be a pool of cash for several investors in India. Mutual funds are one among the important investments that a lot of investors get good offers to take a position in. The securities purchased by the investors are referred because of the fund’s portfolio. Mutual funds give opportunities to small investors to require part within the capital market with none high risk. This study was conducted to research and compare the performance of various sorts of mutual funds in India and concluded that equity funds outperform income funds. This study further concludes that equity fund managers possess significant market timing ability and institutions funds managers are ready to time their investments, but brokers operated funds didn't show market timing ability. Further, it's been found empirically that fund managers are ready to time their investments with the conditions within the market, and possess significant timing ability.